A bar-retained overdenture as an external fixator device in a three-dimensional CAD/CAM-based surgical reconstruction of the mandible. Issue 8 (October 2015) - Koch, Felix P.; Götze, Elisabeth; Kumar, Vinay V.; Schulz, Peter; Wentaschek, Stefan; Wagner, Wilfried
Abstract: Large defects of the human face often cause esthetic as well as functional disorders. We present a new technique for reconstruction of the mandible with prosthodontic rehabilitation in a single surgery, using the implant-supported, bar-retained overdenture as an external fixator. A 58-year-old patient presented with a near total defect of the mandible after cancer resection. For rehabilitation, the mandibular condyles were virtually positioned in the centre of the fossae, and four dental implants were planned. The position of the fibula segments as well as their angulation and lengths were adapted to the implant position. To transfer this plan into surgery, a combined cutting/implant drilling guide was computer-aided printed. To provide the correct angulation of the fibula segments, a CAD/CAM dental arch-bar was made from titanium, fulfilling three functions: to bear the provisional prosthesis; to stabilize the molded fibula as an external fixator; and to position the complete fibula with the prosthesis in a correct relation to the upper jaw and occlusion, as indicated by the prosthesis. This innovative approach of combined prosthodontic and reconstructive rehabilitation could shorten the total reconstruction/rehabilitation time and avoid the need for additional extended surgeries.